Iron deficiency screening is a key issue in chronic inflammatory diseases: A call to action. (3rd May 2022) - Cacoub, Patrice; Choukroun, Gabriel; Cohen‐Solal, Alain; Luporsi, Elisabeth; Peyrin‐Biroulet, Laurent; Peoc'h, Katell; Andrieu, Valérie; Lasocki, Sigismond; Puy, Hervé; Trochu, Jean‐Noël
Abstract: Iron deficiency is frequent in patients with chronic inflammatory conditions (e.g., chronic heart failure, chronic kidney disease, cancers, and bowel inflammatory diseases). Indeed, high concentrations of inflammatory cytokines increase hepcidin concentrations that lead to the sequestration of iron in cells of the reticuloendothelial system (functional iron deficiency). Iron parameters are often assessed only in the context of anemia, but iron deficiency, even without anemia, is present in about half of patients with inflammatory conditions. Iron deficiency worsens underlying chronic diseases and is an independent factor of morbidity and mortality. In daily practice, the most effective biomarkers of iron status are serum ferritin, which reflects iron storage, and transferrin saturation, which reflects the transport of iron. Serum ferritin is increased in an inflammatory context, and there is still no consensus on the threshold to be used in chronic inflammatory conditions. Nevertheless, recent recommendations of international guidelines agreed to define iron deficiency by serum ferritin <100 µg/L and/or transferrin saturation <20%. Iron parameters remain, however, insufficiently assessed in patients with chronic inflammatory conditions. Indeed, clinical symptoms of iron deficiency, such as fatigue, are not specific and often confused with those of the primary disease. Iron repletion, preferably by the intravenous route to bypass tissue sequestration, improves clinical signs and quality of life. Because of the negative impact of iron deficiency on chronic inflammatory diseases and the efficacy of intravenous iron repletion, screening of iron parameters should be part of the routine examination of all patients with chronic inflammatory diseases. Abstract :